Orientations of Al4C3 and Al films grown on GaAs substrates. (1st August 2019) - Pokharel, Nikhil; Smaglik, Nathan; Ahrenkiel, Phil; Giussani, Alessandro; Slocum, Michael A.; Hubbard, Seth M.
Abstract: A method for growth of aluminum epilayers on III-V substrates using metalorganic chemic vapor deposition (MOCVD) processes could be beneficial for optoelectronic and photovoltaic device fabrication. However, deposition from common precursors under standard MOCVD conditions results in polycrystalline Al4 C3 . Both Al4 C3 films grown on GaAs (100) substrates, and those grown on GaAs (111) B substrates, show strong alignment of the rhombohedral [110] for the Al4 C3 crystallites with the in-plane GaAs <110> directions. However, by using plasma-enhanced MOCVD at low growth temperatures, elemental Al can be deposited. Al growth by this method on (001), (111) B and (110) GaAs substrates gave textured, polycrystalline films. In all cases, the Al crystallites are primarily oriented with a <110> aligned with an in-plane <110> of the substrate at initial growth stages. These insights may lead towards growth of large-grained or epitaxial Al films.